Effect of Dispersoid Volume and T6 Heat Treatment on the Tribological Behaviour of Spray-Formed 2014Al-SiCp Composites - Chandra J.; Rao L.S.; Ojha S.N. (My University, 2025)
In the present investigation, the dry sliding wear behaviour of as spray deposited and T6 heat-treated conditions of 2014Al-SiCP composites were studied. A pin-on-disc type wear setup used wherein the applied load varied until the seizure of the sample. The wear behaviour of composites containing different volume fraction of SiC compared to that their respective heat treated composites. Microstructural characterization showed that the second phase particles are distributed along the grain boundaries as well as within the equiaxed grains of the primary α-phase. A significant improvement observed in the hardness of the spray-deposited material after T6 heat treatment resulting in wear and seizure resistance of the base alloy and composites. The wear rate data indicated an optimum SiC volume % for both the as-spray deposited composites and heat treated composites which would maximize the wear resistance. The analysis of the wear surfaces and wear debris particles carried out by using Scanning Electron Microscopy. The results provided evidence of the removal of material by two-body and three-body abrasion with consequent damage of the sliding surface of the specimen. The wear surfaces consisted of grooves and mechanically adhered material. The severity of ploughing was found to be lower at lesser applied load and more importantly, for T6 heat treated material. Combined analysis of the adhered material on the wear surfaces and the corresponding wear debris showed that material removed consists of metallic particles, oxide particles and SiC reinforcements. The complexities involved at the interface during the wear process of composite materials have brought into the discussion. © 2021, Springer Nature B.V.